(untitled) (Impetus, 2021)
The article addresses three key issues that attempt to account for the complex and intricate paths that pass the learning process. To do this, at first it will seek to establish the epistemological relationship between formation and experience, offering clues to rethink how these processes go through the course of existence. Then, seek to provide some meanings of the journey as the possibility of personal transformation and also as essential to confront and deepen the private contents of experience condition. Finally, see in this process, a must to try to draw the links between educational resource and cultures.